Prevalence of Y chromosome microdeletion in azoospermia factor subregions among infertile men from West Bengal, India. Issue 10 (24th August 2021) - Dutta, Saurav; Paladhi, Pranab; Pal, Samudra; Bose, Gunja; Ghosh, Papiya; Chattopadhyay, Ratna; Chakravarty, Baidyanath; Ghosh, Sujay
Abstract: Background: Etiology of male infertility is intriguing and Y chromosome microdeletion within azoospermia factor (AZF) sub‐regions is considered major cause. We conducted a screening for Y chromosome microdeletion in an infertile male cohort from West Bengal, India to characterize Y chromosome microdeletion among infertile men. Methods: We recruited case subjects that were categorized on the basis of sperm count as azoospermia (N = 63), severe oligozoospermia (N = 38), and oligozoospermia (N = 17) and compared them with age, demography, and ethnicity matched healthy proven fertile control males (N = 84). Sequence Tagged Site makers and polymerase chain reaction based profiling of Y chromosome was done for AZF region and SRY for cases and controls. Results: We scored 16.1% of cases (19 out of 118) that bear one or more microdeletions in the studied loci and none among the controls. The aberrations were more frequent among azoospermic males (17 of 19) than in severe oligozoospermic subjects (2 of 19). Conclusion: Our study provides the results of screening of the largest Bengali infertile men sample genotyped with the maximum number of STS markers spanning the entire length of Y chromosome long arm. Y chromosome microdeletion is a significant genetic etiology of infertility among Bengali men. Abstract : Y chromosome microdeletion (YCMD) is a major genetic cause of infertility in men but not yet explored in the Bengali population from India. We characterized YCMD among infertile Bengali men with microsatellite markers and found this may be causative factors of azoospermia and severe oligozoospermia.